In vivo imaging of vascular adhesion protein 1 - preclinical studies with positron emission tomography - Autio, Anu (Annales Universitatis Turkuensis D 1006, 2012)
The golden standard in nuclear medicine imaging of inflammation is the use of radiolabeled leukocytes. Although their diagnostic accuracy is good, the preparation of the leukocytes is both laborious and potentially hazardous for laboratory personnel. Molecules involved in leukocyte migration could serve as targets for the development of inflammation imaging agents. An excellent target would be a molecule that is absent or expressed at low level in normal tissues, but is induced or up-regulated at the site of inflammation. Vascular adhesion protein-1 (VAP-1) is a very promising target for in vivo imaging, since it is translocated to the endothelial cell surface when inflammation occurs. VAP-1 functions as an endothelial adhesion molecule that participates in leukocyte recruitment to inflamed tissues. Besides being an adhesion molecule, VAP-1 also has enzymatic activity. In this thesis, the targeting of VAP-1 was studied by using Gallium-68 (68Ga) labeled peptides and an Iodine-124 (124I) labeled antibody. The peptides were designed based on molecular modelling and phage display library searches. The new imaging agents were preclinically tested in vitro, as well as in vivo in animal models. The most promising imaging agent appeared to be a peptide belonging to the VAP-1 leukocyte ligand, Siglec-9 peptide. The 68Ga-labeled Siglec-9 peptide was able to detect VAP-1 positive vasculature in rodent models of sterile skin inflammation and melanoma by positron emission tomography. In addition to peptides, the 124I-labeled antibody showed VAP-1 specific binding both in vitro and in vivo. However, the estimated human radiation dose was rather high, and thus further preclinical studies in disease models are needed to clarify the value of this imaging agent. Detection of VAP-1 on endothelium was demonstrated in these studies and this imaging approach could be used in the diagnosis of inflammatory conditions as well as melanoma. These studies provide a proof-of-concept for PET imaging of VAP-1 and further studies are warranted.